Is pain tolerance in boxers altered by nucleotide polymorphism rs6746030 in the SCN9A gene? - Leznicka, K.; Gronek, P.; Kurzawski, M.; Cieszczyk, P.; Malinowski, D.; Zmijewski, P. (Archives of Budo, 2018)
Background and Study Aim: In sport, pain plays a pivotal but dual role which is still not fully understood and requires closer cooperation between specialists in the fields of sports medicine, sports science and psychology. The aim of this study was the knowledge about the possible association between rs6746030 (G/A substitution) genotype variants and pain tolerance in boxers.